2016
DOI: 10.3390/app6090265
|View full text |Cite
|
Sign up to set email alerts
|

Dry Sintered Metal Coating of Halloysite Nanotubes

Abstract: Abstract:Halloysite nanotubes (HNTs) are a naturally-occurring aluminosilicate whose dimensions measure microns in length and tens of nanometers in diameter. Bonding defects between the alumina and silica lead to net negative and positive charges on the exterior and interior lumen, respectively. HNTs have been shown to enhance the material properties of polymer matrices and enable the sustained release of loaded chemicals, drugs, and growth factors. Due to the net charges, these nanotubes can also be readily c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Halloysite nanotubes (HNTs) are cyto-and biocompatible 20 . They have attracted increasing attention in biomedical research due to its physicochemical stability, the potential for chemically modification, and ease of doping substances within its lumen, including therapeutic agents [21][22][23][24] , enzymes 25 , nucleic acid 26 , and metal nanoparticles 27 . In addition, HNTs have been proven to enhance mechanical properties for numerous materials, such as alginate 25 , chitosan 28,29 , epoxy 30 , nylon 24 , rubber 31 , and calcium phosphate 32 .…”
Section: Introductionmentioning
confidence: 99%
“…Halloysite nanotubes (HNTs) are cyto-and biocompatible 20 . They have attracted increasing attention in biomedical research due to its physicochemical stability, the potential for chemically modification, and ease of doping substances within its lumen, including therapeutic agents [21][22][23][24] , enzymes 25 , nucleic acid 26 , and metal nanoparticles 27 . In addition, HNTs have been proven to enhance mechanical properties for numerous materials, such as alginate 25 , chitosan 28,29 , epoxy 30 , nylon 24 , rubber 31 , and calcium phosphate 32 .…”
Section: Introductionmentioning
confidence: 99%
“…[27][28][29][30] Structurally, halloysite nanoclay is a two-layered aluminosilicate with water molecules in between and a hollow tubular structure with walls formed through the rolling of 15 to 20 aluminosilicate layers. 27,29,[31][32][33] The outer shell, which is built out of silicium dioxide with free hydroxy groups on the surface, can easily be modied and presents itself therefore as an ideal substrate. 33 The size of the tubes varies from 50 to 70 nm in external diameter and 10 to 20 nm in lumen diameter.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, several recent studies have demonstrated that HNTs are cytocompatible [20,[24][25][26]. In one study, HNTs were added to cultures of epithelial adenocarcinoma and human breast cancer cells up to a concentration as high as 75 µg/mg) and cell proliferation was not affected [24].…”
Section: Introductionmentioning
confidence: 99%
“…In one study, HNTs were added to cultures of epithelial adenocarcinoma and human breast cancer cells up to a concentration as high as 75 µg/mg) and cell proliferation was not affected [24]. In fact, most studies have shown that the HNTs do not produce cytotoxic effects [20,[24][25][26]. Recently, Cervini-Silva et al in 2012 showed that HNTs also have anti-inflammatory properties [27].…”
Section: Introductionmentioning
confidence: 99%